Peranan Umkm Di Kecamatan Cibeber, Kota Cilegon Terhadap Pendapatan Dan Tingkat Kesejahteraan Para Pelaku Umkm - Vera Maria; Annisa Fitriyani; Fitriyani; Bagus Ridho Hikmawan; Shahnaz Mawaria; Muhamad Ridho Wajdi; Tabina Nasywa Nur Fatma (Pusat Riset dan Inovasi Nasional, 2024)
. This study aims to analyze the role of Micro, Small, and Medium Enterprises (MSMEs) in Cibeber Sub-district, Cilegon City, in increasing the income and welfare of the actors. MSMEs play an important role in the local economy, creating jobs and improving community welfare. Through a descriptive qualitative approach, this study collected data from MSME players in Cibeber to evaluate their economic impact. The results show that MSMEs contribute significantly to income generation, which in turn improves the welfare of business owners in terms of economy, education, health and quality of life. Factors such as access to capital, entrepreneurship training and government support play a key role in the success of MSMEs